2022
DOI: 10.1037/xge0001241
|View full text |Cite
|
Sign up to set email alerts
|

No need to choose: Independent regulation of cognitive stability and flexibility challenges the stability-flexibility trade-off.

Abstract: Adaptive behavior requires the ability to focus on a current task and protect it from distraction (cognitive stability), as well as the ability to rapidly switch to another task in light of changing circumstances (cognitive flexibility). Cognitive stability and flexibility have been conceptualized as opposite endpoints on a stability-flexibility trade-off continuum, implying an obligatory reciprocity between the two: Greater flexibility necessitates less stability, and vice versa. Surprisingly, rigorous empiri… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
6
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 94 publications
2
6
0
Order By: Relevance
“…However, none of the higher-order interactions were observed reliably, in that switch costs were not consistently modulated by the proportion congruent manipulation or by task phases across the experiments (mean switch cost by experiment, phase, and task are displayed in Table A3). This observation runs counter to expectations that increased task focus would lead to larger switch cost (e.g., Dreisbach, 2012; Goschke, 2003) but it aligns well with findings from another recent study, wherein the authors concurrently manipulated the proportion of congruent trials and of switch trials in a task switching protocol similar to the one used in the current study (Geddert & Egner, 2022). Akin to the results presented here, there was no effect of the rate of congruent trials on switch costs (and no effect of the rate of switch trials on congruent effect) in that study (Geddert & Egner, 2022), which suggests that switch costs and congruency effects can in principle be independent of each other (reviewed in Egner, 2023).…”
Section: Discussionsupporting
confidence: 60%
See 3 more Smart Citations
“…However, none of the higher-order interactions were observed reliably, in that switch costs were not consistently modulated by the proportion congruent manipulation or by task phases across the experiments (mean switch cost by experiment, phase, and task are displayed in Table A3). This observation runs counter to expectations that increased task focus would lead to larger switch cost (e.g., Dreisbach, 2012; Goschke, 2003) but it aligns well with findings from another recent study, wherein the authors concurrently manipulated the proportion of congruent trials and of switch trials in a task switching protocol similar to the one used in the current study (Geddert & Egner, 2022). Akin to the results presented here, there was no effect of the rate of congruent trials on switch costs (and no effect of the rate of switch trials on congruent effect) in that study (Geddert & Egner, 2022), which suggests that switch costs and congruency effects can in principle be independent of each other (reviewed in Egner, 2023).…”
Section: Discussionsupporting
confidence: 60%
“…The RT data of Experiments 1a and b fully conformed to our expectations about baseline and learning phase performance, and thus allowed the crucial question of transfer of demand settings to be tested. Specifically, the two tasks elicited equivalent cross-task congruency effects at baseline, the RT task by congruency interaction effects in the baseline phase were nonsignificant in all experiments: 1a (p = .77), 1b (p = .55), 2a (p = .69), 2b (p= .71), 3 (p = .71), and the learning phase successfully induced the expected proportion congruent effect, whereby mean congruency effects were significantly reduced for the low proportion congruent compared to the high proportion congruent task, replicating classic proportion congruent effects (e.g., Braem et al, 2019;Bugg & Crump, 2012) in the domain of cross-task interference (e.g., Geddert & Egner, 2022). The subsequent transfer phase revealed that the proportion congruent effects (and by inference, the level of focus associated with each task) during the learning phase persisted.…”
Section: Discussionmentioning
confidence: 82%
See 2 more Smart Citations
“…In line with this argument, Geddert and Egner (2022) recently showed that different measures of cognitive flexibility versus stability during task switching—the switch costs and the task rule congruency effect—are affected independently from each other with an orthogonal manipulation of the respective contextual demands (i.e., proportion of task switches and proportion of incongruent trials). They ascribed this finding to the different mechanisms that account for switch costs on the one side and congruency effects on the other.…”
Section: Discussionmentioning
confidence: 81%